Evaluation of Passive Films on 17-7PH and 410 Stainless Steel Exposed to NaCl Solution - Martínez Aparicio, Brisa Selene; Gaona Tiburcio, Citlalli; Almeraya Calderón, Facundo; Goldsberry, Reece; Castaneda, Homero (Molecular Diversity Preservation International, 2024)
This work covers the formation of a passive state for two different alloys used in the aeronautical industry. The aim of this study is to investigate the effectiveness of passivation treatments on 17-7PH and 410 SS (stainless steel) samples, specifically when performed with citric and nitric acid solutions at 49 °C using an immersion time of 90 min and subsequent exposure in 3.5 wt.% NaCl solution. Employing the cyclic potentiodynamic polarization (CPP) technique, the corrosion properties of the passivated material were evaluated according to the ASTM G65-11 standard. A microstructural analysis was performed using scanning electron microscopy (SEM). The passivated layer was characterized via X-ray photoelectron spectroscopy. In the results, the CPP curves showed positive hysteresis, indicating pitting localized corrosion, and 17-7PH steel passivated at 49 °C for 90 min in citric acid exhibited lower corrosion rate values equivalent to ×10−3 mm/year.